2022
DOI: 10.3390/tomography8040141
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Atherosclerotic Plaque in Cerebral Artery Stenosis According to High-Resolution MR Imaging

Abstract: Atherosclerosis can affect multiple arteries, and result in stroke and heart disease. Clinical and conventional imaging is insufficient to predict the progression of atherosclerosis. This study investigates risk factors that rely on high-resolution magnetic resonance imaging (HR-MRI). Patients with cerebral artery stenosis who had undergone HR-MRI at least twice were included. The demographics, risk factors, and proportion of patients with cerebral artery stenosis were investigated. The association between ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In addition, they showed that progression of IPH was related with progression of the plaque. This could be meaningful in predicting individual plaque risks [ 37 ]. In that way, we could learn more on plaque inflammation in relation to time and over different locations throughout the arterial vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they showed that progression of IPH was related with progression of the plaque. This could be meaningful in predicting individual plaque risks [ 37 ]. In that way, we could learn more on plaque inflammation in relation to time and over different locations throughout the arterial vasculature.…”
Section: Discussionmentioning
confidence: 99%